Establididad factorial de dos Test psicológicos: D.A.T. y Kuder - Fogliatto, Hermelinda M. (Revista Interamericana de Psicología/Interamerican Journal of Psychology, 2017)
This study was designed to investigate the internal structure of two test batteries which were administered in two consecutive years. The first battery included the Differential Aptitude Test the Kuder Preference Record (Form Ch.) and the Minnesota Multiphasic Personality Inventory; the second included the DAT and the Kuder, and the Maudsley Personality' Inventory instead o f the MMPI. A factor analysis of these data using the method of principal axes resulted in four and three factor, respectively, which were further investigated through the varimax rotation of the principal axes factors.